Citizen monitoring promotes informed and inclusive forest governance in Liberia - Christensen, Darin (Proc Natl Acad Sci U S A, 2021)
Global forest loss depends on decisions made in the rural, often poor communities living beside the Earth’s remaining forests. Governance problems in these forest-edge communities contribute to rapid deforestation and household vulnerability. In coordination with experimental studies in 5 other countries, we evaluate a program that recruits, trains, and deploys citizens to monitor communal forestland in 60 communities in rural Liberia. The year-long intervention is designed to promote more informed and inclusive resource governance, so that that citizens’ preferences (and not just leaders’ interests) are reflected in forest management. In our control communities, households are uninformed and disengaged; leaders’ authority is unchecked. The program both engages and mobilizes community members: households are better informed and participate more in the design and enforcement of rules around forest use. They also report receiving more material benefits from outside investors’ activities in their community forests. The chiefs who lead these communities attest to strengthened accountability. Using both on-the-ground environmental assessments and remotely sensed data, we find no effects on forest use or deforestation. Households do not favor more conservation, and, thus, more inclusive management does not reduce forest use. Conservation likely requires compensating community members for foregoing forest use; citizen monitoring, we argue, could ensure that such schemes enjoy popular support and do not just benefit local elites.